[RETRACTED] Adoption of Principal Instructional Management Rating Scale (PIMRS) for Effective Instructional Delivery in Nigerian Secondary Schools (International Online Journal of Language, Communication, and Humanities (INSANIAH), 2025)
Retraction Notice The article titled: "Adoption of Principal Instructional Management Rating Scale (PIMRS) for Effective Instructional Delivery in Nigerian Secondary Schools" Originally published on pages 38 to 60 in this issue has been formally retracted and removed from the journal archive at the request of the author. The editorial board has approved this retraction in line with our publication ethics policy. This article is no longer considered part of the published academic record. The page range is preserved to maintain the integrity of the issue’s structure.